Promotion Strategy Using Online Digital Media at Food Stall Putri - Edy Yulianto Putra; Melisa Putri Pane (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
The spread of the Covid-19 pandemic throughout the world, including Indonesia, has caused most daily activities to be replaced by an online system. This creates an urgency for MSMEs to implement business marketing through digital systems. This study aims to create and implement the best business strategy in today's digital era for Warung Putri based in Batam, Indonesia. This business strategy is to create a printed menu and start implementing digital marketing using Instagram as a social media platform. The results of the study show that the printed menu and the implementation of digital marketing through Instagram have increased user brand awareness of the products of female stalls which hold an important key for business customers database growth.